2018
DOI: 10.1177/0265407518815775
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style and perceived discrimination: Associations with depression among young lesbian, gay, and bisexual Romanian adults

Abstract: Purpose: This study aims to evaluate the importance of individual determinants (gender, age), attachment style, and perceived discrimination on depression among young lesbian, gay, and bisexual (LGB) Romanians. Method: Participants comprised 374 young adults (172 men and 202 women; mean age = 25.75, SD = 7.78; 216 LGB and 158 heterosexuals). They completed the Adult Attachment Scale, the Beck Depression Inventory, and underwent a structured interview, designed to classify clinical depression, and measure the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…In line with the literature's findings on adult attachment and same-sex relationships' well-being (e.g., Sommantico et al 2020;Fingerhut and Peplau 2013;Guzmán-González et al 2019;Mohr et al 2013;Popa-Velea et al 2019; Starks and Parsons 2014;Wright 2020), the results of our study showed a positive correlation between attachment insecurity and lower levels of relationship satisfaction. In fact, participants with insecure attachment patterns showed lower levels of relationship satisfaction, thus confirming the hypothesis regarding the important role of the attachment system in relationship satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the literature's findings on adult attachment and same-sex relationships' well-being (e.g., Sommantico et al 2020;Fingerhut and Peplau 2013;Guzmán-González et al 2019;Mohr et al 2013;Popa-Velea et al 2019; Starks and Parsons 2014;Wright 2020), the results of our study showed a positive correlation between attachment insecurity and lower levels of relationship satisfaction. In fact, participants with insecure attachment patterns showed lower levels of relationship satisfaction, thus confirming the hypothesis regarding the important role of the attachment system in relationship satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, these research findings indicate the relevance of deeply understanding the association between adult attachment and relationship satisfaction in Italian sexual minority populations, taking into account the stated influence of minority stress on adult attachment and relationship satisfaction (e.g., Sommantico et al 2018;Cao et al 2017;Cook and Calebs 2016;LeBlanc et al 2015;Gonçalves et al 2020;Fassinger 2003, 2006;Popa-Velea et al 2019;Šević et al 2016;Wright 2020). We can do so by focusing in particular on the role played by differentiation of self, a variable whose role has never been analyzed in sexual minority populations.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Globally, in the Romanian population, decisions about HPV vaccination seem mostly influenced by negative emotions (possibly generated by the insufficient information provided by the health system and by a negative campaign carried out by mass media [32,34]), which far outweigh the gaps in knowledge about HPV infection and HPV vaccine [35]. Vulnerable women are exposed to an even higher risk of contracting HPV and may feel embarrassed to freely disclose their frail medical and psychological status [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many medical students may lose, throughout studies, the track of their initial motivation to pursue this career [24][25][26], while a gap may occur and widen between the objective evaluation of their abilities and their subjective self-evaluation [27]. This discrepancy may represent an additional reason for self-doubt and unhappiness in students pertaining to vulnerable groups [28,29].…”
Section: Introductionmentioning
confidence: 99%